Development and Validation of a CBT-Based Arabic Question Bank for Secondary Education - Nurul Aini Pakaya; Ibnu Rawandhy N. Hula; Nikma S Abdjul; Adtman A. Hasan; Yousif Abdelmannan Mohamed Godat Arrashedy (UIN Mahmud Yunus Batusangkar, Indonesia, 2025)
The educational process often overlooks the evaluation aspect of learning, as educators frequently develop assessment instruments without adhering to established guidelines, despite evaluation being a critical component in determining the effectiveness and development of education. This study employed a mixed-methods Research and Development (R&D) approach to develop an Arabic question bank for Grade X students at State Islamic High School (MAN) 1 Pohuwato. Quantitatively, logical validity results showed that expert validators awarded a total score of 74 with an average of 3.89, while practitioner validators provided a total score of 71 with an average of 3.74, both categorized as very valid, resulting in a combined average validity score of 3.815. Qualitatively, the high validity values were supported by expert and practitioner evaluations indicating that the test items were clearly formulated, aligned with curriculum competencies, and appropriately represented the intended cognitive levels. Following the validation process, the revised items were tested in two classes, X-A and X-D, involving 36 students. This development research produced a set of 40 Arabic multiple-choice questions ready for use in the Mid-Term Examination (UTS) and Final Examination (UAS). The implications of this study show that CBT-based Arabic question banks can improve the objectivity, efficiency, and quality of Arabic learning evaluation in madrasas.